Elaboração de projeto arquitetônico de uma residência unifamiliar de 76,00 m² contemplando processos construtivos e materiais sustentáveis - VALENTIN, Breno Innocente; CARDOSO, Clara Inoé; MEDRADO, Eduarda Ribeiro; GOUVEIA, Emanueli da Silva; SILVA, Giulia de Lima; SOUSA, Graziela Marques de (098, 2024)
Este trabalho de conclusão de curso teve como objetivo a elaboração de um projeto habitacional de até 80 m², integrando a sustentabilidade no desenvolvimento e execução da construção. A pesquisa abordou aspectos como escolha de materiais e técnicas construtivas para minimizar resíduos, otimização da cadeia produtiva e consumo energético com foco em energias renováveis, além de garantir conforto térmico e acústico. Diante da crescente preocupação com as mudanças climáticas e a escassez de recursos, a pesquisa destaca o impacto positivo de construções sustentáveis, como evidenciado em estudos do USGBC, que apontam reduções significativas no consumo de energia e no destino de resíduos. O trabalho reforça a importância de incorporar práticas sustentáveis na arquitetura, demonstrando que é possível conciliar eficiência ambiental com conforto e funcionalidade.

This thesis aimed to develop a residential project of up to 80 m² that integrates sustainability in both design and construction. The research focused on materials and construction techniques that minimize waste generation, the supply chain of building materials with attention to environmental impact, energy consumption with an emphasis on renewable energy sources, and the provision of thermal and acoustic comfort. In light of the growing concerns about climate change and the depletion of natural resources, the study highlights the positive impact of sustainable construction, as evidenced by the USGBC, which reports significant reductions in energy consumption and waste diversion from landfills. The thesis emphasizes the importance of incorporating sustainable practices into architecture, demonstrating that it is possible to combine environmental efficiency with comfort and functionality.
Development of a modernized project for a 76.00 m² single-family home, including sustainable construction processes and materials
Keywords: Construção civil; Construção civil (aspectos socioambientais); Resíduos de construção; Infraestrutura